2000
DOI: 10.1097/00008390-200008000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of gastrin-releasing peptide in malignant melanoma cells

Abstract: Gastrin-releasing peptide (GRP), the mammalian counterpart of bombesin, was first identified in the nervous system of the gastrointestinal tract. Little is known about its distribution in the human skin or about its function in certain diseases such as malignant melanoma. Recently functional GRP receptors have been found on human melanoma cell lines. We therefore investigated, using immunohistochemistry, whether human melanoma cells express GRP and whether there is a significant change in its distribution amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Melanoma has demonstrated immunoreactivity for several neuropeptides, including alpha‐melanocyte‐stimulating hormone (α‐MSH), galanin adrenocorticotrophic hormone, beta‐endorphin gastrin‐releasing peptide, growth hormone and NPY . However, the relationship of their expression and melanoma prognosis is not well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma has demonstrated immunoreactivity for several neuropeptides, including alpha‐melanocyte‐stimulating hormone (α‐MSH), galanin adrenocorticotrophic hormone, beta‐endorphin gastrin‐releasing peptide, growth hormone and NPY . However, the relationship of their expression and melanoma prognosis is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…17 In cancer, the use of a NPYR1 agonist could synergize to decrease tumour cell growth in vivo in Ewing disease and, on the other hand, using NPYR2 antagonists could therefore be a strategy to treat neuroblastomas. 18 Melanoma has demonstrated immunoreactivity for several neuropeptides, including alpha-melanocyte-stimulating hormone (a-MSH), 19 galanin 20 adrenocorticotrophic hormone, beta-endorphin 21 gastrin-releasing peptide, 22,23 growth hormone 24,25 and NPY. 7 However, the relationship of their expression and melanoma prognosis is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 2 h there is a higher intestinal retention for 99m Tc-BN-1.1p, which by 4 h is similar to 99m Tc-BN-1.1 values (P < 0.05). Apparently, the faster retention of 99m Tc-BN-1.1p to the liver and the intestines compared to 99m Tc-BN-1.1 is probably due to the absence of the amino acid sequence [2][3][4][5][6] which affects the excretion pathway of the truncated radiolabeled peptide, a fact that has been reported in the literature. 24,39,42 In order to investigate whether 99m Tc-BN-1.1 and 99m Tc-BN-1.1p exhibit in vivo selectivity, the radioactivity in pancreas, an organ overexpressing BB2-Rs, was also counted.…”
Section: Synthesismentioning
confidence: 75%
“…All experimental results indicate that the truncated BN sequence (7)(8)(9)(10)(11)(12)(13)(14) can be used in place of the longer (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) sequence, probably with some modifications in order to improve its excretion pathway toward more favorable kidney elimination. Overall, the biological properties exhibited by 99m Tc-BN-1.1 and 99m Tc-BN-1.1p (high affinity for BB2-Rs, rapid internalization, fast delineation of PC-3 experimental tumors, good quality of images) compare favorably to those of other BN derivatives in the literature, indicating a successful design concept that merits further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Data on GRPR expression in human cutaneous MM are very limited. To our knowledge, there is one published series that demonstrates GRPR expression in biopsy material from patients with MM using immunohistochemistry . In the study, 43% of tumour samples found GRPR expression, with positive staining being seen regardless of the Clark Level.…”
Section: Discussionmentioning
confidence: 99%